Analysis of Work Culture, Compensation, and Work Discipline on Job Satisfaction of PT Arya Anantara Cargo Medan - Walulas Karina Asri; Saimara Sebayang; Ikhah Malikhah (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of work culture, compensation, and work discipline on employee job satisfaction at PT Arya Anantara Cargo Medan, both partially and simultaneously. The population in this study was all employees serving as staff (non-managerial) at PT Arya Anantara Cargo Medan, totaling 45 people. Given the relatively small population size, all members of the population were used as research respondents using the census method. Data were collected through questionnaires using a five-point Likert scale. The data analysis method used was multiple linear regression analysis with the assistance of SPSS software, encompassing the t-test (partial), F-test (simultaneous), and coefficient of determination (R²) test. The results showed that partially, work culture had a positive and significant effect on job satisfaction with a t-count of 3.848 > t-table of 2.019 and a significance of 0.000 < 0.05. Work discipline also had a positive and significant effect on job satisfaction with a t-count of 3.437 > t-table of 2.019 and a significance of 0.001 < 0.05. Meanwhile, compensation did not have a significant effect on job satisfaction with a t-count of 1.742 < t-table of 2.019 and a significance of 0.089 > 0.05. Simultaneously, work culture, compensation, and work discipline had a positive and significant effect on job satisfaction with an F-count of 55.404 > F-table of 2.83 and a significance of 0.000 < 0.05. The Adjusted R Square value of 0.788 indicates that the three independent variables were able to explain 78.8% of the variation in employee job satisfaction, while the remaining 21.2% was explained by other factors outside the research model.